Green Synthesis of 4-Nitro-4’-Methoxy Chalcone by Grinding Technique and its Antibacterial Activity - Elfi Susanti V. H.; Sri Mulyani; Sri Retno Dwi Ariani; Suryadi Budi Utomo; Muhammad Hizbul Wathon; Widiastuti Agustina Eko Setyowati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
This research aims to synthesize 4-nitro-4’-methoxy chalcone and determine the potential of 4-nitro-4’-methoxy chalcone as an antibacterial against Staphylococcus aureus and Escherichia coli bacteria. The synthesis of 4-nitro-4’-methoxy chalcone was carried out using the grinding technique, an environmentally friendly green synthesis approach—characterization of the synthesized chalcone using FTIR, 1H-NMR, and 13C-NMR. The research demonstrated that 4-nitro-4’-methoxy chalcone could be synthesized via grinding techniques using 4-methoxyacetophenone, 4-nitrobenzaldehyde, and NaOH as catalysts. The synthetic process achieved higher yields and was environmentally friendly due to the absence of organic solvents. The resulting product was yellow crystalline with a yield of 54.42% and a melting point of 172°C–173°C. Antibacterial activity tests revealed that the synthesized chalcone exhibited greater inhibition against E. coli than S. aureus. This was evidenced by the clear zones formed (9.57 mm for S. aureus and 12.46 mm for E. coli), indicating that 4-nitro-4’-methoxy chalcone possesses strong antibacterial activity.